Implementing IoT system in growth monitoring of Bentong ginger - Lim, Xuan (2024)
In the dynamic landscape of agriculture, Bentong ginger has earned a distinguished status, celebrated not only for its aromatic and culinary attributes but also cherished for its myriad medicinal benefits. However, the cultivation of this versatile plant encounters formidable challenges, particularly concerning limited land availability and protracted crop cycles. In response to these impediments, our proposed solution introduces an innovative IoT framework that harnesses the capabilities of state-of-the-art hardware components. This includes the utilization of the Raspberry Pi, sensors, and actuators, collectively forming a responsive and adaptable environment tailored for the optimal growth of Bentong ginger. This precision agriculture project addresses these challenges by developing an integrated IoT-based system tailored for precise environmental monitoring and automated cultivation management. The problem statement highlighted the need for a more efficient and sustainable approach to ginger cultivation, considering factors such as air temperature, humidity, light levels, soil moisture, and nutrient composition. The developed system encompasses a comprehensive data collection mechanism, leveraging high-quality sensors to gather real-time environmental data critical for optimal ginger growth. This data is then processed and analyzed to provide actionable insights, guiding automated adjustments to environmental conditions. Automation features include dynamic control of lighting, ventilation, watering, and fertilizing, all tailored to maintain optimal growth conditions for Bentong ginger. The system's operation is further enhanced by intuitive visualization tools, including dashboards and graphs, offering users a clear and comprehensive overview of the environmental conditions and growth trends. This enables informed decision-making, facilitating efficient management and optimization of cultivation processes. In short, this project offers a holistic solution to the challenges of Bentong ginger cultivation, combining advanced IoT technologies, automation capabilities, and data-driven insights to foster sustainable and efficient cultivation practices.